Hubungan Persentase Sel Leukosit Polimorfonuklear dalam Cairan Serebrospinal dan Luaran Pasien Meningitis Tuberkulosis di RSUP Dr. Hasan Sadikin Bandung - Amanda Widayanti; Ahmad Rizal Ganiem; Ida Parwati (Faculty of Medicine, Universitas Padjadjaran, 2020)
Tuberculous (TB) meningitis is the most severe type of extrapulmonary TB with high morbidity and mortality rates. Many factors affect patient outcome, including the intracranial inflammation process. In acute inflammation, recruitment of a high number of polymorphonuclear (PMN) cells can cause edema which may eventually increase the intracranial pressure. This increase in intracranial pressure may lead to functional decline, disability, and even death. This study aimed to explore the association between the PMN percentage in cerebrospinal fluid (CSF) and TB meningitis patient outcome as measured by the Glasgow Outcome Scale at Dr. Hasan Sadikin General Hospital Bandung, which is a tertiary hospital in Indonesia. This was a retrospective cohort study using patient medical record data from 2017. All TB meningitis patients over 18 years old were included. Patients with missing PMN results in medical record were excluded, which led to a total 88 subjects participating in this study. Variables analyzed were PMN percentage in CSF and patient outcome that were categorized as poor, moderate, and good. Analysis were performed using theKruskal-wallis test. An increase in PMN median as the patient outcome declined were observed, but the association between the PMN percentage in CSF and patient outcome was insignificant (p=0.186). Hence, no association between PMN percentage in CSF and TB meningitis patient outcome was identified in this study. Hubungan Persentase Sel Leukosit Polimorfonuklear dalam Cairan Serebrospinal dan Luaran Pasien Meningitis Tuberkulosis di RSUP Dr. Hasan Sadikin BandungMeningitis tuberkulosis (TB) merupakan merupakan jenis TB ekstraparu paling berat dengan morbiditas dan mortalitas tinggi. Berbagai faktor memengaruhi luaran pasien, salah satunya proses inflamasi intrakranial. Pada inflamasi akut, terjadi peningkatan sel polimorfonuklear (PMN) dan bila dalam jumlah tinggi dapat menimbulkan efek edema yang meningkatkan tekanan intrakranial. Peningkatan tekanan intrakranial ini menyebabkan penurunan fungsi otak, disabilitas, bahkan kematian. Penelitian ini bertujuan mengetahui hubungan persentase PMN dalam cairan serebrospinal (CSS) dan luaran Glasgow Outcome Scale pada pasien meningitis TB di RSUP Dr. Hasan Sadikin Bandung. Penelitian ini merupakan studi retrospektif cohort menggunakan data rekam medik tahun 2017. Kriteria inklusi adalah pasien terdiagnosis meningitis TB dan berusia ≥18 tahun. Kriteria eksklusi adalah data rekam medik yang tidak lengkap untuk hasil PMN. Variabel yang diteliti adalah persentase PMN dan luaran pasien yang dikategorikan menjadi GOS buruk, sedang, dan baik kemudian dianalisis dengan uji Kruskal-wallis. Didapatkan 88 subjek yang memenuhi syarat. Terdapat peningkatan median PMN seiring derajat perburukan luaran namun hasil analisis menunjukkan tidak terdapat hubungan yang bermakna antara PMN dan luaran GOS pasien (p=0,186). Simpulan, tidak terdapat hubungan antara persentase PMN dalam CSS dengan luaran GOS pasien meningitis TB.